Productivity and Profitability Layer Chicken Farm Using Small Scale Feed Mill Production in Sidrap Regency, South Sulawesi, Indonesia - Irmasusanti; Isbandi; Prasetiyono, B.W.H.E.; Siregar, A.R. (International Journal of Poultry Science, 2013)
The objective of this research was to determine differences in productivity and profitability of layer poultry farm that used small scale feed mill production quality Indonesia National Standard (SNI) and not based on SNI. The research survey was conducted to 30 layer farmers in Sidrap district that used feed produced by small scale factory by interview and observation. Primary and secondary data obtained were used to answer the research objective. Respondences characteristic, productivity, revenue, production costs and income were recorded for two months. Descriptive statistic and one sample t-test were used to analyze the data. Layer chicken farmer that used small scale feed mill produced generally raising chickens with business scale less than 5,000 chickens. Quality of productivity and productivity of layer chicken farm that used small scale mini feed mill produced was suited to SNI, significantly different (p>0.01) compared to one that wasn’t based on SNI.